Genomic Insights Into Plant-Growth-Promoting Potentialities of the Genus Frankia - Nouioui, Imen; Cortés-albayay, Carlos; Carro, Lorena; Castro, Jean Franco; Gtari, Maher; Ghodhbane-Gtari, Faten; Klenk, Hans-Peter; Tisa, Louis S.; Sangal, Vartul; Goodfellow, Michael (Frontiers in Microbiology, 2019)
This study was designed to determine the plant growth promoting potential of members of the genus Frankia. To this end, the genomes of 21 representative strains were examined for genes associated directly or indirectly with plant growth. All of the Frankia genomes contained genes that encoded for products associated with the biosynthesis of auxins (indole-3-glycerol phosphate synthases, anthranilate phosphoribosyltransferases [trpD], anthranilate synthases and aminases [trpA and B]), cytokinins (11 well conserved genes within the predicted biosynthetic gene cluster), siderophores, and nitrogeneases (nif operon except for atypical Frankia) as well as genes that modulate the effects of biotic and abiotic environmental stress (eg. alkyl hydroperoxide reductases, aquaporin Z, heat shock proteins). In contrast, other genes were associated with strains assigned to one or more of four host specific clusters. The genes encoding for phosphate solubilization (eg. low-affinity inorganic phosphate transporters), lytic enzymes (eg. cellulases) were found in Frankia cluster 1 genomes, while other genes were found only in cluster 3 genomes (eg. alkaline phosphatases, extracellular endoglucanases, pectate lyases) or cluster 4 and cluster 1c genomes (eg. NAD(P) transhydrogenase genes). Genes encoding for chitinases were found only in the genomes of the type strains of Frankia casuarinae, F. inefficax, F. irregularis and F. saprophytica. In short, these in silico genome analyses provide an insight into the plant growth promoting abilities of Frankia strains of known taxonomic provenance. This is the first study designed to establish the underlying genetic basis of cytokinin production in Frankia strains. Also, the discovery of additional genes in the biosynthetic gene cluster involved in cytokinin production opens up the prospect that Frankia may have novel molecular mechanisms for cytokinin biosynthesis.